Restoring T Cell Homeostasis After Allogeneic Stem Cell Transplantation; Principal Limitations and Future Challenges - Moutuou, Moutuaata M.; Pagé, Gabriel; Zaid, Intesar; Lesage, Sylvie; Guimond, Martin (Frontiers in Immunology, 2018)
For several leukemia patients, allogeneic stem cell transplantation (SCT) is the unique therapeutic modality that could potentially cure their disease. Despite significant progress made in clinical management of allogeneic SCT, acute graft-versus-host disease (GVHD) and infectious complications remain the second and third cause of death after disease recurrence. Clinical options to restore immunocompetence after allogeneic SCT are very limited as studies have raised awareness about the safety with regards to graft-versus-host disease. Pre-clinical works are now focusing on strategies to improve thymic functions and to restore the peripheral niche that have been damaged by alloreactive T cells. In this mini review, we will provide a brief overview about the adverse effects of GVHD on the thymus and the peripheral niche and the resulting negative outcome on peripheral T cell homeostasis. Finally, we will discuss the potential relevance of coordinating our studies on thymic rejuvenation and improvement of the peripheral lymphoid niche to achieve optimal T cell regeneration in GVHD patients.